Mucormicosis Rino-Orbito-Cerebral asociada a COVID-19. Reporte de caso y revisión de la literatura (International Journal of Medical and Surgical Sciences, 2023)
Acute invasive fungal rhinosinusitis is a rare infectious condition with high mortality rates (50- 80%), characterized by primary angioinvasion, thrombosis, ischemia, and necrosis. It can be caused by Zygomycetes fungi (such as Mucor) and Aspergillus. It is observed in immunocompromised patients, such as poorly controlled diabetics, hematologic malignancies, undergoing chemotherapy, acquired immunodeficiency syndrome, and transplant recipients. This case report presents a case of Rhino-Orbito-Cerebral Mucormycosis in a patient with a history of Severe Acute Respiratory Syndrome due to the novel coronavirus, followed by a review of the relevant literature.
Keywords: Rinosinusitis fúngica invasiva; Mucormicosis Rino-Orbito-Cerebral; Post-COVID; Anfotericina B